Chemical composition, antioxidant and antitumor activities of sub-fractions of wild and cultivated Pleurotus ferulae ethanol extracts - Yi Yang; Changshuang Fu; Fangfang Zhou; Xiaoyu Luo; Jinyu Li; Jun Zhao; Jiang He; Xiaoqin Li; Jinyao Li (PeerJ, 2018)
Pleurotus ferulae is an edible and medicinal mushroom with various bioactivities. Here, the ethanol extracts of wild and cultivated P. ferulae (PFEE-W and PFEE-C) and their subfractions including petroleum ether (Pe-W/Pe-C), ethyl acetate (Ea-W/Ea-C) and n-butanol (Ba-W/Ba-C) were prepared to evaluate their antioxidant and antitumor activities. Both PFEE-W and PFEE-C show the antioxidant activity and PFEE-W is stronger than PFEE-C. The antioxidant activities of their subfractions are in the following order: Ea > Ba > Pe. Moreover, PFEE-W and PFEE-C significantly inhibit the proliferation of murine melanoma B16 cells, human esophageal cancer Eca-109 cells, human gastric cancer BGC823 cells and human cervical cancer HeLa cells through induction of apoptosis, which partially mediated by reactive oxygen species. The antitumor activities of their subfractions are in the following order: Ea ≥ Pe > Ba. Pe-W shows higher antitumor activity compared with Pe-C, which might be correlated with the difference of their components identified by gas chromatography-mass spectrometry. These results suggest that both wild and cultivated P. ferulae have antioxidant and antitumor activities, and cultivated P. ferulae could be used to replace wild one in some functions.